The Potential Effect of Honey-derived D-Allulose in Counteracting Hyperglycemia by Time and Dose Dependent Manner in Diabetes Mellitus - Sari, Flori R. (Jurnal Kimia Valensi, 2023)
Diabetes mellitus has become a worldwide burden due to its persistent, chronic hyperglycemia. D-allulose, a monosaccharide sugar with a 180.16 molecular weight, is widely used as a low-calorie sweetener, is not involved in glucose-related metabolism, and thus does not alter insulin and pancreatic function. This study aimed to evaluate the potential role of honey-derived D-allulose in acute and sub-chronic diabetes mellitus. Diabetic Sprague-Dawley rats were divided into 9 groups and treated with 0.1, 0.2, and 0.4 g/kg BW honey-derived D-allulose for 28, 56, and 84 days. Post-prandial blood glucose levels and body weight were measured every 4 weeks. Significant reductions in post-prandial blood glucose levels were observed on days 56 and 84 treatment with 0.1 g/kg BW D-allulose. More significant reductions were observed on days 28, 56, and 84 of treatment with 0.2 or 0.4 g/kg BW D-allulose. Eighty-four days of treatment with 0.4 g/kg BW D-allulose significantly reduced post-prandial blood glucose levels compared to all groups. We identified that honey-derived D-allulose reduced post-prandial blood glucose levels in a dose- and time-dependent manner. Thus, honey-derived D-allulose may provide beneficial support for diabetic conditions not only as a sweetener but also as a pharmacological treatment.